2010
DOI: 10.1007/s11295-010-0335-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA markers linked to eastern filbert blight resistance in “Ratoli” hazelnut (Corylus avellana L.)

Abstract: Eastern filbert blight (EFB), caused by the pyrenomycete Anisogramma anomala (Peck) E. Müller, is a major disease problem and production constraint in orchards of European hazelnut (Corylus avellana L.) in Oregon's Willamette Valley. Host genetic resistance is viewed as the most economical means of controlling this disease. A dominant resistance gene from "Gasaway" has been used extensively in the hazelnut breeding program at Oregon State University, but concern about the durability of a single resistance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Disease resistance is often involves several loci and pathways; the resistance and susceptibility to EFB displayed in certain accessions ( Table 4) is highly unlikely to involve the same genes. For example, the EFB resistance locus in the Spanish accession 'Ratoli' maps to a different linkage group than that of the cultivar 'Gasaway' and may offer a more robust source of resistance (22,51). Variation in nucleotide sequences among hazelnut populations in different geographic regions, have the potential to introduce polymorphisms in coding loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease resistance is often involves several loci and pathways; the resistance and susceptibility to EFB displayed in certain accessions ( Table 4) is highly unlikely to involve the same genes. For example, the EFB resistance locus in the Spanish accession 'Ratoli' maps to a different linkage group than that of the cultivar 'Gasaway' and may offer a more robust source of resistance (22,51). Variation in nucleotide sequences among hazelnut populations in different geographic regions, have the potential to introduce polymorphisms in coding loci.…”
Section: Discussionmentioning
confidence: 99%
“…This resolution allows genome-wide analyses of molecular variation and additional marker discovery to accelerate molecular breeding in hazelnut. For example, the EFB-resistance in 'Gasaway' was previously assigned to LG6 (22), and the separate gene responsible for resistance in the Spanish cultivar 'Ratoli' segregates on LG7 (51). In addition, the recently characterized accession OSU 759.010 transmits resistance via a locus on LG2 (53) different from locations of other identified resistance loci.…”
Section: Discussionmentioning
confidence: 99%
“…Various C. avellana cultivars, seedlings, and interspecific hybrids have since displayed resistance to EFB in Oregon and are now being used in breeding. The most notable EFB-resistant C. avellana include 'Ratoli' and 'Culpla' from Spain, 'Crevenje' and 'Uebov' from Serbia, OSU 495.027 from southern Russia, OSU 408.040 from Minnesota, USA, CCOR 187 from Finland, and OSU 759.010 from Georgia, which is discussed in more detail later in this article (Chen et al, 2005(Chen et al, , 2007Colburn et al, 2015;Coyne et al, 1998;Lunde et al, 2000;Sathuvalli et al, 2009Sathuvalli et al, , 2010Sathuvalli et al, , 2011a. Additional EFB-resistant seedling selections from Turkey, Russia, and Crimea have also more recently been identified at OSU that merit further testing (Mehlenbacher, personal communication, November 19, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Selections of C. avellana have been found that exhibit qualitative or quantitative resistance to EFB (Capik and Molnar, 2012;Capik et al, 2013;Chen et al, 2005Chen et al, , 2007Lunde et al, 2000Lunde et al, , 2006Mehlenbacher et al, 1991;Muehlbauer et al, 2014;Sathuvalli et al, 2010Sathuvalli et al, , 2011aSathuvalli et al, , 2011bSathuvalli et al, , 2012. 'Gasaway' was the first C. avellana cultivar observed to express a very high level of resistance to EFB (Cameron, 1976).…”
mentioning
confidence: 99%
“…Many types of markers have been investigated in hazelnut, including random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP), and microsatellite, the latter also known as simple sequence repeat (SSR) markers (Chen et al, 2005;Davis and Mehlenbacher, 1997;Mehlenbacher et al, 2004;Sathuvalli et al, 2011aSathuvalli et al, , 2011bSathuvalli et al, , 2012. The RAPD markers 152 800 and 268 580 are routinely used in marker-assisted selection (MAS) for EFB resistance from 'Gasaway' (Davis and Mehlenbacher, 1997;Mehlenbacher et al, 2004).…”
mentioning
confidence: 99%